PEMENJARAAN: PE(AB)NORMALAN BUDAYA? - Alie Humaedi; Yulius Panon Pratomo; Rudi Ronald Sianturi (LIPI Press, 2005)
Prison (restraint) is a room derived from the society’s interpretation and experience in order to rehabilitate, remedy, retribution, normalize, and social reintegration. This is a practical explanation of the concept of justice and democracy. The available room is export room. The delegated room to the number of authoritative subjects represents the entire communities to rehabilitate the deviate person from expectations and in order to normalize the morality. It is likely to say not only that those who under control are those whose no place in social area, but also that the authorities in this project may feel fettered due to becoming the thrown-people attendant directly.